The Effect of Service Quality, Products, Transaction Security, and Ease of Use of the Platform on Customer Satisfaction in E-Commerce - Nita Anggreyani (Journal of Digital Business and Data Science, 2025)
Data was collected through a survey involving 200 respondents (100 consumers and 100 entrepreneurs) from users of e-commerce platforms in Indonesia. Multiple linear regression analysis was employed to examine the relationships between variablesin building customer trust and supporting satisfaction. Overall, the results of this study confirm that to create a satisfying shopping experience, e-commerce companies must pay attention to the balance between service quality, product, ease of use, and transaction security. The results of this study also show that customer trust in transaction security is an important factor that should not be ignored in increasing customer satisfaction and loyalty. Therefore, e-commerce companies need to invest in better security systems and transparent policies to protect customers' personal data and ensure smooth transactions.